Pelestarian Budaya Lokal Melalui Lomba Solo Song dan Tari Tingkat SD, SMP, dan Umum Se-Nagari Sijunjung sebagai Bentuk Pengabdian Masyarakat Mahasiswa KKN - Khairuddin .; Amelia Okta Fiana; Gilviona .; Yuyun Azima Sundami; Muhammad Fatah Al Majid (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
This community service activity was carried out by KKN students in Nagari Sijunjung through solo song and dance competitions for elementary, junior high school, and general participants from January 30 to February 1, 2026. The program aimed to provide a platform for the community to express their artistic talents while preserving Minangkabau local culture. Based on field observation, the community showed strong interest in culture but lacked sufficient spaces to sustain it. The activity involved participants from various educational levels and the general public, with high enthusiasm from the audience. The results indicate increased community participation, greater self-confidence among participants, and stronger appreciation for traditional arts. This activity shows that art competitions can serve as an effective medium for local culture preservation through participatory community service.